The Asian Financial Crisis In Malaysia Repercussions At The Firm Level In Manufacturing Sector - Wai, Tham Chee (2004)
This study is to measure the repercussions of the financial crisis at the firm level in Malaysia's manufacturing sector after 5 years since the onset of financial crisis.